Bilingual Education Programs: One more step on the route to a bilingual Costa Rica - Vargas González, María Fernanda (2024)
Since 1994, Costa Rica has been making efforts to improve the knowledge of a second language in primary and secondary school students. Nevertheless, the results have not been as expected. This article aims to study the relevance and need to create education bilingual programs in Costa Rica in disciplines, such as Mathematics. For this purpose, a qualitative approach was used. Documentary review, interviews with experts, and a survey was conducted to potential employers of future graduates. The efforts made by the government to improve bilingual education, both in primary and secondary levels, stand out; however, these have not been sufficient to achieve the desired level of language proficiency in students. Experts agree that there is a need in the country for education professionals with a mastery of the English language in subjects that can potentially be taught in English. Although it is not the only factor, the lack of trained human resources to take on this task has made difficult the appointment of teachers in experimental bilingual schools. That situation has not allowed them to become bilingual schools, and it has even led to the hiring of English teachers to teach mathematics or science.